1980
DOI: 10.1111/j.1751-0813.1980.tb05623.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Birth in the Pathogenesis of Meningeal Haemorrhage and Congestion in Newborn Lambs

Abstract: SUMMARY: In a controlled experiment, term lambs born of caesarean sacrifice, normal or artificially prolonged birth were examined at autopsy to determine the role of vaginal birth in the pathogenesis of presumed birth injury to the fetal CNS characterised by subdural and extradural haemorrhage, subarachnoid haemorrhage and congestion, and blood‐stained cerebrospinal fluid in and around the cranial and spinal meninges of lambs dying during or within 7 days of birth. Additional material, comprising near‐term fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…During parturition, the foetus is subjected to a number of physical and physiological insults. Purely physical factors are likely to be responsible for shearing of blood vessels (Haughey 1980) resulting in major subdural haemorrhage. This author suggested that band haemorrhage in the spinal cord may stem from excessive craniovertebral skeletal movement.…”
Section: Discussionmentioning
confidence: 99%
“…During parturition, the foetus is subjected to a number of physical and physiological insults. Purely physical factors are likely to be responsible for shearing of blood vessels (Haughey 1980) resulting in major subdural haemorrhage. This author suggested that band haemorrhage in the spinal cord may stem from excessive craniovertebral skeletal movement.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a technique that eliminated other causes of death because of extensive field observations. While this technique may overestimate lamb deaths due to cold exposure, it is still considered to be more accurate than the autopsy method originally developed by McFarlane (1965) which underestimates cold‐related deaths (Alexander 1985) and overestimates deaths from dystocia (Haughey 1980).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that injury, manifested by vascular abnormalities, to the fetal central nervous system (CNS) resulted from trauma and/or asphyxia during birth and was the primary cause of perinatal lamb mortality (Haughey 1975). In further work, that author assessed brain injury by the presence of meningeal haemorrhage on the brain (Haughey 1980). It was also concluded that haemorrhages in the meninges, brain congestion and oedema, neuronal ischemic necrosis and intraparenchymal haemorrhages could explain most lamb deaths at birth and within 6 days of birth (Dutra et al 2007).…”
Section: Introductionmentioning
confidence: 98%